Endogenous Retroviruses Provide Protection Against Vaginal HSV-2 Disease - Jayewickreme, Radeesha; Mao, Tianyang; Philbrick, William; Kong, Yong; Treger, Rebecca S.; Lu, Peiwen; Rakib, Tasfia; Dong, Huiping; Dang-Lawson, May; Guild, W. Austin; Lau, Tatiana J.; Iwasaki, Akiko; et al. (Frontiers in Immunology, 2022)
Endogenous retroviruses (ERVs) are genomic sequences that originated from retroviruses and are present in most eukaryotic genomes. Both beneficial and detrimental functions are attributed to ERVs, but whether ERVs contribute to antiviral immunity is not well studied. Here, we used herpes simplex virus type 2 (HSV-2) infection as a model and found that Toll-like receptor 7 (Tlr7-/-) deficient mice that have high systemic levels of infectious ERVs are resistant to intravaginal HSV-2 infection, compared with wildtype C57BL/6 mice. We deleted the endogenous ecotropic murine leukemia virus (Emv2) locus on the Tlr7-/- background (Emv2-/-Tlr7-/-) and found that Emv2-/-Tlr7-/- mice lose protection against HSV-2 infection. Intravaginal application of purified ERVs prior to HSV-2 infection delays disease in both wildtype and highly susceptible interferon-alpha receptor-deficient (Ifnar1-/-) mice. We did not observe enhanced type I interferon (IFN-I) signaling in the vaginal tissues from Tlr7-/- mice, and instead found enrichment in genes associated with extracellular matrix organization. Together, our results revealed that ERVs modulate the vaginal epithelium and protect mice against vaginal HSV-2 infection and delays disease.